90Y Liver Radioembolization Imaging Using Amplitude-Based Gated PET/CT. (May 2017) - Osborne, Dustin R.; Acuff, Shelley; Neveu, Melissa; Kaman, Austin; Syed, Mumtaz; Fu, Yitong
Abstract : Abstract: The usage of PET/CT to monitor patients with hepatocellular carcinoma following 90 Y radioembolization has increased; however, image quality is often poor because of low count efficiency and respiratory motion. Motion can be corrected using gating techniques but at the expense of additional image noise. Amplitude-based gating has been shown to improve quantification in FDG PET, but few have used this technique in 90 Y liver imaging. The patients shown in this work indicate that amplitude-based gating can be used in 90 Y PET/CT liver imaging to provide motion-corrected images with higher estimates of activity concentration that may improve posttherapy dosimetry.